An Exploration of the Experiences and Educational Needs of Patients With Failed Back Surgery Syndrome Receiving Spinal Cord Stimulation. Issue 3 (19th November 2018) - Ryan, Cormac G.; Eldabe, Sam; Chadwick, Raymond; Jones, Susan E.; Elliott‐Button, Helene L.; Brookes, Morag; Martin, Denis J.
Abstract : Objective: To explore the experience of spinal cord stimulation (SCS) for patients with failed back surgery syndrome (FBSS). Methods: Adults with FBSS referred for SCS underwent semistructured interviews at three time points: before their SCS trial, after the trial, and three months after receiving the SCS implant. The face‐to‐face interviews were audio recorded, transcribed verbatim and analyzed thematically. Results: Twelve adults (8 male, 4 female, aged 38–80 years, pain duration 1–26 years) were recruited. Six themes were identified; 1) What should I expect? 2) Varied outcomes, 3) Understanding pain and this new treatment, 4) Experiences of the SCS journey, 5) Getting used to the device, and 6) Finding out what I need to know. Participants' expectations were varied and the procedures were broadly viewed as minor surgery. Participants' expectations about SCS were not limited to pain relief and included reductions in medication, better sleep, and increased physical activity. Participants' understanding of pain and how SCS purports to work was limited. Throughout the process, practical challenges were identified such as the surgical wound management and battery recharging. Participants received information from multiple sources and identified a range of key information needs including a quick‐start guide on how to operate the device and a list of dos and don'ts. Conclusions: Overall, participants' understanding of SCS was limited. The value participants placed on understanding of the process varied markedly. A list of practical informational needs has been identified. Bespoke, user‐friendly, informational tools should be developed from this list to enhance the patient experience of SCS. Keywords: Failed back surgery syndrome, neuromodulation, patient experience, qualitative research, spinal cord stimulation